A breath of fresh air: a quality-improvement study comparing an air-circulating technique versus conventional technique to prevent nasogastric tube dysfunction. Issue 1 (December 2015) - Bani Hani, Murad; Ihim, Ikenna; Harps, Joyce; Cunningham, Steven
Abstract Background Nasogastric tubes are an important component of care in patients with gastrointestinal obstructions. However, they are prone to malfunction despite conventional flushing techniques, with potentially severe consequences. There is no widely accepted, gold-standard way to ensure that a nasogastric tube succeeds in maintaining an empty stomach following flushing. Methods We have developed a flushing technique to better ensure successful tube function. We compared this technique to conventional flushing both in vitro (using a plastic stomach model) and in vivo (in a pig model), and we provide a didactic video. Results The mean gastric residual volume following our novel flushing technique is nearly 25-fold lower than following conventional flushing (13 mL vs. 330 mL). Conclusions Our simple technique is more effective than conventional techniques in maintaining nasogastric tube function and therefore should prevent dangerous vomiting and aspiration pneumonia better than conventional techniques.